Diagnostic Value of Vascular Endothelial Growth Factor C (VEGF-C) and CA 15-3 in Breast Cancer - Ajeng Kurnia Wardhani; Indranila Kustarini Samsuria; Meita Hendrianingtyas; Edward Kurnia Setiawan Limijadi; Ria Triwardhani (Journal of Biomedicine and Translational Research, 2021)
ABSTRACT Background: expression of VEGF-C and CA 15-3 may be useful to differentiate between malignant and benign breast tumour because VEGF-C plays a role in promoting angiogenesis and lymphangiogenesis in malignant processes and CA 15-3 is the soluble form of transmembrane protein MUC1, a tumour marker which shows higher expression in breast cancer.Objective: to determine the diagnostic value of VEGF-C and CA 15-3 as tumour markers in patients with breast cancer.Methods: this diagnostic study recruited 76 patients that underwent surgical biopsy procedures at Dr. Kariadi and Pantiwilasa Citarum Hospitals Semarang. The VEGF-C and CA 15-3 levels in blood specimens taken before surgical biopsy procedure was determined using ELISA method. An ROC curve and AUC were used to establish the cut-off points and diagnostic value. Pathology examination results from the biopsy specimens were used as the gold standard.Results: the cut-off value for VEGF-C and CA 15-3 were 989.50 pg/mL and 74.00 U/mL. Sensitivity for VEGF-C, CA 15-3 and VEGF-C+CA 15-3 were 76.6%, 64.1% and 89.1%. Specificity for VEGF-C, CA 15-3 and VEGF-C+CA 15-3 were 75.0%, 75.0% and 50.0%. The AUC for VEGF-C, CA 15-3 and VEGF-C+CA 15-3 was 0.831 (95% CI = 0.727-0.934), 0.742 (95% CI = 0.628-0.856) and 0.840 (95% CI = 0.742-0.938).Conclusion: VEGF-C in combination with CA 15-3 is the best diagnostic parameter for breast cancer and has the best accuracy as a tumour marker for breast cancer.